Age of second language acquisition in multilinguals has an impact on gray matter volume in language-associated brain areas - Kaiser, Anelis; Eppenberger, Leila S.; Smieskova, Renata; Borgwardt, Stefan; Kuenzli, Esther; Radue, Ernst-Wilhelm; Nitsch, Cordula; Bendfeldt, Kerstin (Frontiers in Psychology, 2015)
Numerous structural studies have established that experience shapes and reshapes the brain throughout a lifetime. The impact of early development, however, is still a matter of debate. Further clues may come from studying multilinguals who acquired their second language at different ages. We investigated adult multilinguals who spoke three languages fluently, where the third language was learned in classroom settings, not before the age of 9 years. Multilinguals exposed to 2 languages simultaneously from birth (SiM) were contrasted with multinguals who acquired their first two languages successively (SuM). Whole brain voxel based morphometry revealed that, relative to SuM, SiM have significantly lower grey matter volume in several language-associated cortical areas in both hemispheres: bilaterally in medial and inferior frontal gyrus, in the right medial temporal gyrus and inferior posterior parietal gyrus, as well as in the left inferior frontal gyrus. Thus, as shown by others, successive language learning increases the volume of language-associated cortical areas. In brains exposed early on and simultaneously to more than one language, however, learning of additional languages seems to have less impact. We conclude that - at least with respect to language acquisition - early developmental influences are maintained and influence experience-dependent plasticity well into adulthood.